From simulations to measurements: prototyping an antenna for non‐linear applications at sub‐THz frequencies. Issue 3 (5th December 2016) - Pigeon, Melusine; Sushko, Oleksandr; Donnan, Robert S.; Kreouzis, Theo; Parini, Clive G.; Wang, Hui; Alderman, Byron; Huggard, Peter G.; Dubrovka, Rostyslav
Abstract : The simulated characterisation and tuning of prototype antennas prior to manufacture is described in this study. The antennas incorporate Schottky diodes so as to frequency triple incident sub‐THz power. Such a dual frequency, non‐linear, device has been called a multenna. A metrology is outlined for ease of multiple measurements to permit exploring scenarios of multenna element design. Four options are optimally oriented and assembled onto an appropriately dimensioned tile substrate to minimise mutual coupling during characterisation of each element individually. Transmission measurements of the multennas are performed at 100 and 300 GHz: an example of resonant behaviour is presented.